Akinetic mutism following prefrontal injury by an electrical grinder a case report: A diffusion tensor tractography study. Issue 6 (February 2018) - Jang, Sung Ho; Kim, Seong Ho; Lee, Han Do
Abstract: Rationale: A 72-year-old male had suffered from head trauma resulting from injury to his frontal area by an electrical grinder while working at his home. Patient concerns: He lost consciousness for approximately 10 minutes and experienced continuous post-traumatic amnesia. Diagnoses: He was diagnosed as traumatic intracerebral hemorrhage in both frontal lobes, intraventricular hemorrhage, and subarachnoid hemorrhage, and underwent decompressive craniectomy and hematoma removal. Interventions: The patient's Glasgow Coma Scale score was 5. At 2 months after onset, when starting rehabilitation, he showed no spontaneous movement or speech; he remained in a lying position all day with no spontaneous activity. Outcomes: On 2-month diffusion tensor tractography, decreased neural connectivity of the caudate nucleus to the medial prefrontal cortex (PFC, Broadmann area [BA]: 10 and 12) and orbitofrontal cortex (BA 11 and 13) was observed in both hemispheres. Lessons: Akinetic mutism following prefrontal injury.